Permintaan Penggantian Atas Dasar Subrogasi oleh PT. A Sebagai Penanggung Kepada PT. P Sebagai Pengangkut Sekaligus Pemilik Kapal - Putra, Rhezar Adinanda (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2019)
Abstract – The purpose of the study is as a graduation requirement to earn a Bachelor Degree in Law of the Faculty of Law in University of Surabaya. The practical purpose of the thesis is to understand if PT. A as an insurer was entitled to get compensation from PT. P as a carrier and ship owner based on subrogation, eventhough PT. P was supposed to be free from any claims pursuant to transportation agreement between PT. P and HS. After that, an accident occurred because of force majeure. HS did not ask PT. P for compensation, instead HS filed insurance claims to PT. A as an insurer based on insurance agreement between them. After that, PT. A paid compensation to HS and received a letter of subrogation from HS. Based on that letter of subrogation, PT. A asked compensation to PT. P, eventhough PT. P was supposed to be free from any claims from accident caused by forced majeure pursuant to transportation agreement between PT. P and HS. Keywords: Insurance Agreement, Compensation, Transportation Agreement, Subrogation